Evaluasi Efektivitas Tata Kelola Teknologi Informasi Di Rumah Sakit Umum Daerah Provinsi Nusa Tenggara Barat Dengan Menggunakan Kerangka Kerja Cobit 2019 - Muh. Yusril Hidayat; Agung Budi Susanto (Universitas Pamulang, 2025)
Hospitals have a strategic responsibility to improve the quality of public health services. However, information technology (IT) management in hospitals often faces challenges such as lack of long-term planning, which causes information to be inefficient and ineffective. This study aims to evaluate the effectiveness of information technology governance at the West Nusa Tenggara Provincial Hospital using the COBIT 2019 framework. The focus of the study includes risk management (APO 12), change management (BAI 06), and security service management (DSS 05). The method used is a case study with a qualitative approach, involving interviews and questionnaires for data collection. The evaluation results show that the current average capability level is 2.5 with a target of 3. Key findings include the need for improvement in risk management and security services. Recommendations for improvement include the development of new risk policies, staff training, and adoption of the latest security technology. Implementation of COBIT 2019-based suggestions is expected to improve the quality of services and performance of information technology at the NTB Provincial Hospital.